PENERAPAN METODE RESITASI DISERTAI TEKNIK OPERAN KERTAS IDE TERHADAP HASIL BELAJAR IPA SMPN 2 LENGAYANG KABUPATEN PESISIR SELATAN - Dera, Afri - (Pendidikan Biologi, 2014)
The use of method which was less varied, the lack of texbook provided and the students, low learning achievement in Biology especially on the pollution of the environment topic in class VII of SMPN 2 Lengayang in Academic Year 2013/2014 were the reasons for which this research was conducted. To overcome the problem, recitation method assisted with ideas paper passing technique was applied. This research was aimed at revealing whether the use of recitation method assisted with ideas paper passing technique could improve the students, learning achievement in Biology in class VII of SMPN 2 Lengayang. This was an ekperimental research which used Randomized Control Group Posstest Only Design. The population of this research was all of students in class VII of SMPN 2 Lengayang registered in Academic Year 2013/2014. By using Purposive Sampling technique, class VII.b was chosen as the ekperimental class and class VII.d was as the control group. The result of the research showed that the average score of the students in the experimental class 75,26 was higher than that of students in the control class 60,93. The result of the hypothesis test indicated that the value of tcalculated 4,50 was smaller than ttable 1,67 showing that the hypothesis was accepted. Thus, it was concluded that the use of recitation method assisted with ideas paper passing technique could improve the students, learning achievement in Biology in class VII of SMPN 2 Lengayang Kabupaten Pesisir Selatan.